Analysis of Language Style in Kabar Cirebon Sport News - Iim Mughafiroh; Indrya Mulyaningsih; Itaristanti Itaristanti (ppjbsip, 2019)
A news reporter has different characters in writing news or has their own characteristics in writing news. This study analyzes sports news in terms of the form and meaning of language style, as well as the dominant form that is characteristic in writing sports news in Cirebon News. This research uses a qualitative research approach. The data in this study were sourced from the November 2018 edition of Kabar Cirebon. This study uses several stages of data analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are 71 forms of language style in the Cirebon news sports news. In this case, 71 forms of language style, there are 13 types of language styles, namely one form of language style of erotesis, one form of language style of cynicism, one form of language style of eponyms, one form of language style of pleonasm, two forms of style of language antonomasia, one form of language style asindeton, five forms of polysindeton language style, 14 forms of sinekdoke language style, six forms of epithetic language style, five forms of prolepsis language style, 17 forms of metaphorical language style, four forms of anticlimax language style, and 8 forms of climax language style. The meaning contained in each form of language style has its own meaning and is related to one another. The dominant form of language used in sports news in Kabar Cirebon is the form of a metaphorical style of language.